Diffusion of CO2 in Magnesite under High Pressure and High Temperature from Molecular Dynamics Simulations - Lei Liu; Longxing Yang; Chunqiang Zhuang; Guangshu Yang; Li Yi; Hong Liu; Fengxia Sun; Xiaoyu Gu; Hanyu Wang (Geofluids)
CO2 transports in the Earth’s interior play a crucial role in understanding the deep carbon cycle and the global climate changes. Currently, CO2 transports inside of the Earth under extreme condition of pressure and temperature have not been understood well. In this study, the molecular dynamics (MD) calculations were performed to study CO2 transports under different CO2 pressures in slit-like magnesite pores with different pore sizes at 350~2500 K and 3~50 GPa are presented. Diffusion of CO2 in magnesite was improved as the temperature increases but showed the different features as a function of pressure. The diffusion coefficients of CO2 in magnesite were found in the range of 9×10−12 m2 s−1~28000×10−12 m2 s−1. Magnesite with the pore size of 20~25 Å corresponds to the highest transports. Anisotropic diffusion of CO2 in magnesite may help to understand the inhomogeneous distribution of carbon in the upper mantle. The time of CO2 diffusion from the mantle to Earth surface was estimated to be around several tens of Ma and has an important effect on deep carbon cycle. The simulation of CO2 transports based on the Earth condition provides new insights to revealing the deep carbon cycle in the Earth’s interiors.